Not just citronella, Super Melissa! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Citronella, or lemon balm, is the generic name for certain aromatic grasses that grow in tropical areas and are used in cooking, and production of perfumes and pharmaceuticals. It has many medicinal values, although they are not well known....